Parris's standard form of building contract : JCT 98. - Chappell, David (David M.); Parris, John. (Oxford : Blackwell Science, 2002)
This book on the main form of building contract, JCT 98, has always occupied a unique position as being both an authoritative yet readable, guide to the contract provisions, and the legal background to the form. The new edition includes new case law.
Preface / John Parris -- Ch. 1. Background to the contract, the documents and some key provisions -- Ch. 2. The role of the architect and quantity surveyor -- Ch. 3. The contractor's obligations -- Ch. 4. Sub-contractors, suppliers and statutory undertakers -- Ch. 5. Certificates, payments and retention -- Ch. 6. Variations and their valuation -- Ch. 7. Liquidated damages and extension of time -- Ch. 8. Insurance provisions -- Ch. 9. Determination before completion -- Ch. 10. Claims and counterclaims -- Ch. 11. Dispute resolution -- Ch. 12. Practical completion, defects liability period, the final account.
Previous edition published as: The standard form of building contract / John Parris. London : Collins, 1985.
Includes index.
Print version record.
John Wiley and Sons
Keywords: Construction contracts -- Great Britain; TECHNOLOGY & ENGINEERING -- Construction -- Contracting; Construction contracts; Great Britain